2017
DOI: 10.1016/j.commatsci.2017.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Newly synthesized Zr 2 AlC, Zr 2 (Al 0.58 Bi 0.42 )C, Zr 2 (Al 0.2 Sn 0.8 )C, and Zr 2 (Al 0.3 Sb 0.7 )C MAX phases: A DFT based first-principles study

Abstract: The structural, elastic, and electronic properties of newly synthesized Zr 2 (Al 0.58 Bi 0.42 )C, Zr 2 (Al 0.2 Sn 0.8 )C, and Zr 2 (Al 0.3 Sb 0.7 )C MAX nanolaminates have been studied using firstprinciples density functional theory (DFT) calculations for the first time. Theoretical Vickers hardness has also been estimated for these compounds. All the calculated results are compared with experimental data and also with that of recently discovered Zr 2 AlC phase, where available. Zr 2 (Al 0.58 Bi 0.42 )C and Zr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 41 publications
(38 reference statements)
1
29
0
Order By: Relevance
“…The recent discovery of a magnetic MAX phase has extended the list of interesting properties of MAX family [7]. To date, a large number of MAX phase compounds have been synthesized [8][9][10][11][12][13][14][15][16][17] and their physical properties have also been studied [18][19][20][21][22][23][24][25][26][27]. Very recently, Lapauw et al has synthesized Hf 3 AlC 2 [28], which is the first member of 312 MAX phases in the Hf-Al-C system.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of a magnetic MAX phase has extended the list of interesting properties of MAX family [7]. To date, a large number of MAX phase compounds have been synthesized [8][9][10][11][12][13][14][15][16][17] and their physical properties have also been studied [18][19][20][21][22][23][24][25][26][27]. Very recently, Lapauw et al has synthesized Hf 3 AlC 2 [28], which is the first member of 312 MAX phases in the Hf-Al-C system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore related quaternary compositions of the type Zr 2 (Al, A I )C where A I  = Sn, Sb, Pb or Bi have also been reported 811 . The latter study has suggested that partial substitutions on the A-site help to stabilize the Zr 2 AlC phase.…”
Section: Introductionmentioning
confidence: 88%
“…The variation in bond length with the applied pressure has a close contact with the bonding characteristics. The 3.282 (LDA) 3.3 10 3.3174 32 14.405 (LDA) 14.6 10 14.6304 32 3.3294 10 3.334 33 14.556 10 14.600 33 3.319 34 14.604 34 3.3183 35 14.6178 35 3.327 36 The available experimental data on Hf-Al-C and Ti-Al-C system are listed for comparison.…”
Section: Structures and Bonding Of Zr-al-c Systemsmentioning
confidence: 99%
“…49 There exist five independent elastic constants for hexagonal structures, c 11 , c 12 , c 13 , c 33 , c 44 and one dependent constant c 66 = (c 11 Àc 12 )/2. The calculated elastic constants, together with the available experimental and theoretical results from others, 6,34,37,41,42 are listed in Table 3. It can be seen that our calculated values are in good agreement with those from the previous studies.…”
Section: Elastic Propertiesmentioning
confidence: 99%